Viral advertising: message quality, trust and consumers intention to share the content in social media. (11th September 2019) - Tsekouropoulos, Georgios
This study aims to determine the factors that affect the intention of viewers to share viral advertising messages. The dissertation starts with the review of the available literature, following by the research methodology, the data analysis and the conclusions. A 2 × 2 between-subjects experimental design will be used and each responded will be assigned to one of the conditions (trustworthy and non-trustworthy company; close friend or random acquaintance). For that reason, a primary research with the use of a questionnaire was conducted and 145 respondents participate on the research. The results among others show that perceived sender trust, perceived advertiser trust, message quality and attitude toward sharing electronic content are not significantly related with the intention of the viewers to share viral advertising messages. On the other hand, frequency of sharing viral advertising messages is affected by the same factors.